2010
DOI: 10.1128/mcb.00464-10
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis of the Aspartic Acid/Glutamic Acid Transporter Dip5 Is Triggered by Substrate-Dependent Recruitment of the Rsp5 Ubiquitin Ligase via the Arrestin-Like Protein Aly2

Abstract: Endocytosis of nutrient transporters is stimulated under various conditions, such as elevated nutrient availability. In Saccharomyces cerevisiae, endocytosis is triggered by ubiquitination of transporters catalyzed by the E3 ubiquitin ligase Rsp5. However, how the ubiquitination is accelerated under certain conditions remains obscure. Here we demonstrate that closely related proteins Aly2/Art3 and Aly1/Art6, which are poorly characterized members of the arrestin-like protein family, mediate endocytosis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
109
0
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(125 citation statements)
references
References 25 publications
8
109
0
8
Order By: Relevance
“…Interestingly, an isoform of mammalian 14-3-3 has also been shown to regulate the Nedd4.2 E3 ubiquitin ligase (20,21), although in this case the binding between these proteins has been reported to be direct and not via adaptor proteins, as in yeast. Although several reports have shown physical interactions between ART family members and specific transporter proteins biochemically (9,10), our data provide the in vivo demonstration of this class of interactions. Importantly, using the BiFC technique, we observe the interaction between Rod1 and both Hxt6 and Hxt1 and show plasma membrane or endocytic vesicle accumulation for the Rod1-Hxt6 and Rod1-Hxt1 complexes, respectively.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Interestingly, an isoform of mammalian 14-3-3 has also been shown to regulate the Nedd4.2 E3 ubiquitin ligase (20,21), although in this case the binding between these proteins has been reported to be direct and not via adaptor proteins, as in yeast. Although several reports have shown physical interactions between ART family members and specific transporter proteins biochemically (9,10), our data provide the in vivo demonstration of this class of interactions. Importantly, using the BiFC technique, we observe the interaction between Rod1 and both Hxt6 and Hxt1 and show plasma membrane or endocytic vesicle accumulation for the Rod1-Hxt6 and Rod1-Hxt1 complexes, respectively.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies have shown that Rod1 is necessary for the down-regulation of Hxt6 when cells are shifted from raffinose to glucose-containing medium (11). At least two studies have presented different experimental evidence showing that ART family members bind directly to transporter proteins (9,10). However, in these cases, in vivo interactions in live cells were not reported, nor were the subcellular localization of the complexes.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…This mode of downregulation, originally illustrated in the case of the inositol permease Itr1 (14), has been described for several metal transporters (Alr1, Zrt1, Smf1 and -2, and Ctr1), the uracil permease Fur4, the phosphate permease Pho84, and the high-affinity hexose transporter Hxt6/7 (15)(16)(17). It has also been reported for Gap1 (18,19) and several other yAAPs, e.g., Can1 (20), Lyp1 (21), Dip5 (22), Tat2 (17), and Mup1 (21). Still, it remains to be determined whether the signal inducing the endocytosis of these yAAPs is the internal accumulation of the transported amino acid (e.g., inhibiting the Npr1 kinase and thereby activating arrestin-like adaptors) or the catalytic process of amino acid transport itself.…”
mentioning
confidence: 96%
“…We next determined whether substrate transport elicits downregulation of other yAAPs. Previous work has shown that the lysine (Lyp1), methionine (Mup1), arginine (Can1), tryptophan (Tat2), and glutamate/aspartate (Dip5) permeases are downregulated when their substrates are provided to cells at high concentration (17,(20)(21)(22). It remains to be determined, however, whether this endocytosis is caused by the process of amino acid transport catalyzed by these permeases, by internal accumulation of the transported amino acid, or by a combination of these effects.…”
Section: Cen-ars Gal1-gap1-167(k9r-k16r)-gfp (Ura3)mentioning
confidence: 99%